Navigating A World of Generative AI: Suggestions for Educators - Cao, Lydia; Dede, Chris (Next Level Lab, Harvard Graduate School of Education, 2023)
Understanding the nature of generative AI is crucial for educators to navigate the evolving landscape of teaching and learning. In a new report from the Next Level Lab, Lydia Cao and Chris Dede reflect on the role of generative AI in learning and how this pushes us to reconceptualize our visions of effective education. Though...Continue Reading Navigating A World of Generative AI: Suggestions for Educators
Keywords: /unread